Legal Hermeneutics in Reforming Preparation of Village Regulation: Case of Indonesia and Timor Leste - Astariyani, Ni Luh Gede; Yusa, I Gede; Hermanto, Bagus; da Cruz, Rosino (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
This study explores the formation and challenges of Village Regulations in three regions: Tabanan, Badung, and Denpasar. It addresses two core objectives: identifying the dynamics of village-level legislation and examining the application of legal hermeneutics in interpreting such regulations. The research combines normative and empirical legal methods, employing a qualitative descriptive analysis through the Statute, Conceptual, and Analytical approaches. The findings reveal persistent issues in the drafting process, particularly inconsistencies with the Ministry of Home Affairs Regulation No. 111 of 2014. These challenges stem from both technical and interpretive shortcomings. The study further emphasizes the importance of hermeneutical interpretation in maintaining normative consistency and avoiding conflicting legal provisions. Additionally, a comparative perspective is offered through an analysis of village governance in Timor-Leste, where village regulations are governed under Law No. 9 of 2016. This research contributes to the discourse on institutional reform and democratic resilience at the village level, highlighting the need for clearer legal frameworks and interpretive consistency in local governance.